Development of inquiry skills through digital game-based learning in subject content - Bónus, Lilla; Nagy, Lászlóné (Iskolakultúra, 2020)
The development of 21st century skills in a learning environment that is inquiry-centered and technology-rich is a highly researched field. This is due to comprehensive skills like problem solving and critical thinking having become emphasized in public education. The standards aiming to develop these 21st century skills support inquiry-based approaches. In an inquiry-based learning environment, students employ their inquiry skills, which are closely connected to both problem solving and critical thinking. Skills of scientific investigation and problem solving are: analysis of problems and phenomena; formulating questions and hypotheses; observation, investigation, designing and performing experiments; identification and control of variables; method selection; data gathering; data presentation and analysis; evaluation, interpretation, communication and presentation of results; and drawing conclusions. Thus, inquiry skills are 21st century skills, so their development is an important task of public education. However, the integration of game elements into inquiry-based learning environment aiming the enhancement of learning outcomes is a new approach. Because of the increased interest, several researchers have proven that a correctly chosen and implemented game can increase students’ content knowledge, is beneficial to attitude and motivation, and can be used for capability development. In this study, inquiry skills, domestic demand for the measurement of inquiry skills, and some possibilities for the development of inquiry skills are discussed first. In the second part, the interpretation of digital game-based learning (DGBL) is reviewed. In the third part, the theory of digital game construction and the connection between digital game-based learning and inquiry skills are presented.